We Roma a critical reader in contemporary art - Baker, Daniel; Hlavajova, Maria (Amsterdam Valiz, 2013)
"We Roma: a critical reader in contemporary art inquires into the contemporary moment through the lens of Roma artistic and intellectual practices, gathering knowledge from the Roma way of life. As the so-called West's misconceptions of itself, inherited from the legacy of the modern, are being unmasked through unprecedented shifts in politics, society, aesthetics, and economics--what can we learn from the commonalities among political struggles of historically marginalized communities such as Roma and in what we know as majority society? With the emblematic claim in the artistic imaginary "we Roma", including in it wider society--how can we invoke the possibility of a different world and alternative futures? Artists, theorists, writers, and activists--both Roma and non-Roma--speculate on such questions and the possibility of art to imagine the world otherwise." -- Provided by publisher
We Roma: notes from a conversation Daniel Baker andMaria Hlavajova -- Reconstruction, recognition, and Roma Albert Atkin -- Homecoming at witching hour: the securitization of the European Roma and the reclaiming of their citizenship -- Minister and ghost: a prophecy Damian James Le Bas and Delaine Le Bas -- Uneasy cohabitation of the established and the outsiders Zygmunt Bauman -- Reclaiming: the camp and the avant-garde Ethel Brooks -- The birth of Roma visual arts--Hungary, 1979 Agnes Daroczi -- I am not here to talk about the "Gypsy Problem" Tony Gatlif -- Required reading Ian Hancock -- Rohrback living memorial, 2005 Sanja Ivekovic -- Yours is an optimistic scenario Timea Junghaus and Maria Hlavajova -- The post-other as avant-garde Bonaventure Soh Bejeng Ndikung and Regina Romhild-- The real crime is ours Salman Rushdie -- Avant-garde/Roma: a critical history of bohemianism and cultural politics.
FA-2910g donated by Ma'am Lisa Ito.
Keywords: Art, modern -- 21st century -- Political aspects; Art, modern -- 21st century -- Social aspects; Art, modern -- 21st century; Art criticism